Controlling variable indirect WCTO as the mediating variable against ROE - Parlina, Nurhana Dhea; Maiyaliza, Maiyaliza; Budianto, Erwin (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
This study aims to examine the direct and indirect effect of current ratio and working capital turn over (WCTO) dan return on Equity (ROE), with WCTO serving as a mediating variable , pharmaceutical sub sector company list on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The Research adopts a quantitative approach using secondary data in the form on annual financial statements. The sample was selected  using purposive sampling resulting in 40 data point from 8 companies. The analytical method use is path analysis support by 25 software. During the observation method, average sales in pharmaceutical sub sector industry show a declining tren leading to decrease in both profit and working capital. However data also indicate the beginning of the new growth in this sector. Therefore this study was conducted in the response to these on  emerging patterns. The result show that WCTO has significant indirect effect on ROE while the current ratio doesnot have a direct impact  on ROE Keywords: Path Analysis; CR; WCTO; ROE; Finance